Effect of Microwave Drying Technology Mode to the Changes of B-Carotene and Lycopene in the Gac Aril - Nguyen, Duc Trung; Nguyen, Ngoc Hoang; Nguyen, Minh He; Hoang, Hai Ha (Old Journal, 2017)
Initial evaluation of the microwave drying (MWD) applicability for the aril of Gac (Momordica cochinchinensis Spreng) shows that the specific power ratio (SPR), drying time, air speed affect to the changes of lycopene of gac aril but they do not affect tothe changes of ẞ-carotene clearly[cite: 5]. The MWD technology mode: 3,25 W/g of SPR, 50 minutes of drying time, 1,1 m/s of air speed affect is suitable to gac aril[cite: 6]; the content obtained byMWD of -carotene and lycopene is corresponding to 5,2±1,2 and 163,7 ±24,6 mg.g^-1 which is distinctively better than thermal convection drying ( 4.7±2.1 and 82.5±12.9 mg.g^-1) but worse than Freeze-drying(7,2±1,3 and 189.6±25.3 mg.g^-1)[cite: 7].